Factors Affecting the Capital Adequacy Ratio (CAR): A Case Study of Joint-Stock Commercial Banks in Vietnam - Nga, Lu Phi; Ha, Doan Thanh (International Journal of Supply Chain Management, 2021)
The commercial banks are constantly implementing capital adequacy to meet Basel standards, primarily through the issuance of bonds to increase tier 2 capital sources to ensure capital safety and mobilize capital. Long-term to meet the market’s borrowing needs. For that reason, this article aims to study the factors affecting the capital adequacy ratio of joint-stock commercial banks in Vietnam to consider the impact of macroeconomic and internal factors. The author has conducted a study the Data from 20 joint-stock commercial banks in Vietnam from 2009 to 2019. The authors used traditional panel data analysis methods, including Pooled OLS, tissue Fixed effects (FEM), random effects (REM) model. The authors had obtained some main results as follows: both economic growth and inflation do not have a positive impact on CAR